Values profile of health career students from Southern Chile - Véliz Burgos, Alex (2017)
Objective: Higher education institutions must include curricular strategies that enable students to make decisions according to the values and principles related to their professions. The objective of this study was to determine the values profile expressed by health career students from Southern Chile. Materials and methods: This is a quantitative cross-sectional descriptive study with a purposive sample of 242 (M = 20.1 years old) nursing, psychology and kinesiology students to whom the Schwartz Value Survey was applied. Software SPSS 20.0 was used to perform a hierarchical clustering analysis and verify the values dimensions associated with each other. One-way ANOVA with post-hoc tests were conducted to verify the means differences among the scores of the values subscales. Results: Two large homogeneous clusters of values were identified. One consisted of the dimensions of Conformity, Security, Achievement, Tradition and Benevolence, and the other one of the dimensions of Hedonism and Stimulation. During the analysis of means, significant statistical differences were observed between the groups in the dimensions of Universalism, Power, Self-Direction, Benevolence, Conformity, Tradition and Achievement (p < 0.01). The most outstanding means differences were those between psychology and nursing students. In the dimensions of Power, Conformity and Tradition, kinesiology and nursing students showed higher means than psychology students (p < 0.01). Conclusions: The results reveal health career students’ values profile. The next step should be to compare those profiles with the values profile of graduates from each discipline, in order to contribute to the strengthening of the dimensions which students from each career consider important for their professional performance.